Race, Gender, and Memes: Reactive Blackness and Teaching the Eighteenth Century - Chow, Jeremy (Lumen)

(untitled) (Canadian Society for Eighteenth-Century Studies / Société canadienne d'étude du dix-huitième siècle, 2022)
This essay interweaves pedagogy, reflection, and critical synthesis to evaluate an assignment employed in the upper-division seminar, “Race and Gender in the Eighteenth Century”: The Meme Museum. The Meme Museum harnesses social media reaction with the goal of orienting students’ responses and readings to eighteenth-century literature. The Meme Museum also ineluctably reproduces “digital blackface” in that students, who attend a Predominately White Institution, rely on Black celebrities and athletes to express their reactive emotions and affects towards the assigned readings. This essay offers the term “reactive blackness” as a communicative media language and affective comportment that emerges directly from an eighteenth-century archive and admits the intersections of race and gender into its fold. Reactive blackness exploits blackened emotionality and reifies the Black experience as an icon of expressivity. The essay thus interrogates artifacts from the student-generated Meme Museum to consider the transhistorical analyses that such an assignment might avail in the anti-racist teaching of race and gender in the eighteenth century.